Implementasi Decanomial Bead Bar Box Untuk Materi Penjumlahan Dan Pengurangan Bilangan Pada Siswa Kelas II SDN Jati 03 (International Forum of Researchers and Lecturers, 2024)
This research aims to not only make students skilled in mathematics but also provide provisions for its application in everyday life. Mathematics learning needs to use concrete objects to help students understand mathematical concepts according to the stage of student learning development, namely at the concrete operational stage. Addition and subtraction of numbers is one of the subjects of mathematics. Students often have difficulty learning addition material using saving techniques and subtraction using borrowing techniques. The use of learning media in the form of concrete objects is very helpful in learning the material of adding and subtracting numbers. One of the learning media that can be used is the decanomial bead bar box. This media is a Montessori-based media. This research aims to describe the implementation of decanomial bead bar box media for addition and subtraction of numbers in class II students at SDN Jati 03 and to describe student learning outcomes in the implementation of decanomial bead bar box media for addition and subtraction of numbers in class II students at SDN Jati 03.